Interrogating teacher leadership development through a formative intervention: a case study in a rural Secondary School in northern Namibia - Iyambo, David Kandiwapa (Rhodes University, Faculty of Education, Department of Education, 2018)
The Namibian education system has undergone major policy shifts from a 'top-down' hierarchical leadership practice to a more shared and democratic form of leadership in schools. These policies compel principals and school management team members to involve level-one teachers in decision-making and other leadership roles within their schools and beyond. However, to this end, the goals envisaged by policies for teachers to participate in, and contribute to the overall school leadership activities and decision-making have not been fully realised. This was due to the inherent hierarchy of the 'top-down' system and autocratic leadership style which remains powerful within the current school practice. Against this backdrop, this study interrogated how teacher leadership can be developed in a rural Secondary School in northern Namibia. The underlying cultural-historical conditions that promoted or constrained teacher leadership development were surfaced. Opportunities for changes in leadership practices through a formative intervention were developed. Cultural Historical Activity Theory (CHAT) was utilised as a theoretical and analytical framework in this study together with Grant's Model of Teacher Leadership (2006; 2008; 2010). Five level-one teachers, two school management members and a school board chairperson were selected as research participants by means of a purposive sampling method. Furthermore, the study used document analysis, semi-structured interviews, questionnaires and change laboratory workshops as main tools for data generation. The findings revealed that participants understood the concept of teacher leadership differently and that teachers in the case study school were leading in all four zones of teacher leadership model (Grant, 2006; 2008; 2012) although their roles differed. However, the study also found that teacher leadership development was mostly intensified by managerial structures. It appeared from the findings of this study that conditions such as the role of the school management team (SMT) members in promoting teacher leadership development, a supportive organisational culture, and provision of learning support amongst staff members through the attendance of workshops emerged as factors promoting the development of teachers as leaders. The study also revealed that there were many cultural and historical tensions that constrained the practice of teacher leadership development in school. Thus, the study argues that limited leadership training and an inherent 'top-down' hierarchical style of leadership was the main underlying systemic causes that constrained teachers to be developed as leaders. Through the change laboratory workshops, the findings suggested that there was a need for continuous professional development initiatives and leadership training, as alternative way for the realisation of teacher leadership development. Finally, a recommendation that leadership aspects should be constituted in pre-and in-service professional development training as an ongoing practice is made.
Keywords: Educational leadership -- Namibia; School management and organization -- Namibia; Teachers -- Training of -- Namibia; Cultural Historical Activity Theory